Using the multi-segmented regression to assess the durability of structural elements of the systems - Кузьмин, В. Н.; Соломенцев, А. В.; Залисский, М. Ю. (Problems of Informatization and Control, 2016)
The paper deals with an approach based on the use of multi-segmented regression to allow evaluationof durability of structural components of systems. Equations for constructing multi-segmentedregression are considered with purpose to solve the problem of samples durability prediction